Primary biliary cirrhosis and chronic active hepatitis: an examination of clinical, biochemical, and histopathological features in differential diagnosis. Issue 9 (September 1985) - Williamson, J M; Chalmers, D M; Clayden, A D; Dixon, M F; Ruddell, W S; Losowsky, M S
Abstract : Seventy four liver biopsies from 59 patients were reviewed by two observers and histologically graded in the absence of clinical information, firstly, to assess the level of agreement with previous diagnoses; secondly, to identify differences between primary biliary cirrhosis and chronic active hepatitis; and, thirdly, to assess the specificity of Shikata orcein staining and antimitochondrial antibody positivity and titre for primary biliary cirrhosis. Thirty six patients with adequate histology were initially selected as typical of primary biliary cirrhosis or chronic active hepatitis; agreement both between observers and with original diagnoses was reached in 26 (72%) (15 with primary biliary cirrhosis (group 1), 11 with chronic active hepatitis (group 2)). In 19 diagnostically difficult patients in whom clinical and original histological findings had been at variance, histological agreement between observers was reached in 17 (group 3) and original underdiagnosis of primary biliary cirrhosis was suggested. The main clinical and histological differences between groups 1 and 2 are discussed in this paper. Although a high grade of positivity for copper associated protein in the Shikata orcein stain was seen only in primary biliary cirrhosis, a high titre of antimitochondrial antibody positivity was not unique to this condition.